Feeding habits and reproductive biology of the glass lizard Ophiodes cf. striatus from subtropical Brazil - Montechiaro, Leandro; Kaefer, Igor L.; Quadros, Felipe C.; Cechin, Sônia Zanini (North-Western Journal of Zoology, 2011)
Based on the analysis of 249 museum-preserved specimens, together with data on captive individuals, the present paper provides information on the diet, morphology, and reproduction of the glass lizard Ophiodes cf. striatus in the subtropical domain, permitting comparisons with previous reports from different localities. This species is a generalist predator feeding on a wide variety of invertebrate taxa. In addition, O. cf. striatus occasionally preys on reptiles, including conspecific individuals. There is no evidence of partitioning of prey types between the sexes or ontogenetic changes. In our study, Aranae was the most important food item in the diet, closely followed by Orthoptera. The total volume of prey, but not the number of prey items in each stomach, was positively correlated with lizard snout-vent length (SVL). Females had greater SVL, whereas males had longer tails and vestigial hind limbs. Female oviductal embryos were recorded between July and December, and parturitions occurred in December. Females had a mean number of eight oviductal embryos, and 11 newborns per litter. Litter size was positively correlated with female SVL. Male spermatogenesis was constant throughout the year, with an increase during the presumed mating period, as evidenced by analyzing the changes in the volume of testes. Hence, the glass lizard showed a seasonal reproductive cycle in the subtropics, which is a general pattern for viviparous species, and has been reported for O. cf. striatus from lower latitudes. © 2011 NwjZ, Oradea, Romania.
Keywords: Anguidae; Invertebrata; Ophiodes Striatus; Orthoptera; Reptilia; Squamata